Effect of sediment type on feed efficiency, growth and survival of Litopenaeus vannamei (Boone, 1931) - doi: 10.4025/actascibiolsci.v33i4.6134 - Santos, Daniele Bezerra dos (2011)
This study aimed to evaluate the zootechnical performance of Litopenaeus vannamei shrimp at different types of unconsolidated substrate. Juvenile shrimp (0.97 ± 0.27 g) were acclimatized, in a stocking density of 52 m-2, to 21 polyethylene boxes (50 L) connected individually to biofilters in a closed water exchange system. The animals were submitted to the treatments: 1) A = 25% silt + 25% clay + 25% very fine sand + 25% fine sand; 2) B = 50% fine sand + 50% very fine sand and 3) Control = no sediment, with seven replications each. Photoperiod was set on 12L: 12D. Shrimps were fed twice a day (at 08:00 and 16:00h) with 12% total biomass day-1. Food was offered in feeding trays 2 cm from the substrate. The experiment had a duration of 48 days, evaluating: apparent ration intake, food efficiency, specific growth rate, survival and weight gain. During this period, water quality was monitored daily. Data was analyzed by Anova or Kuskal-Wallis test, depending on normality (SigmaStat 3.1, 2004 and STATISTICA 6.0, 2001). There were no differences among groups regarding weight gain, food intake, SGR and survival, indicating that these did not exert influence on the zootechnical performance of L. vannamei juvenil.